FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRAKTEK PEMILIHAN MAKANAN JAJANAN DI SEKOLAH DASAR NEGERI 29 PEKANBARUTANGKERANG SELATAN BUKIT RAYATAHUN 2017 - Sherly Vermita Warlenda; - Desnovianti (LPPM Universitas Muhammadiyah Riau, 2018)
FAO (Food and Agriculture Organization) defines snacks as food which are presented or sold in side of road, in a public area, that has been prepared and cooked before at home or at production place. In this case, from 2001 until 2009, the data showed that Elementary students were poisoning as much 1.101 KLBfood poisoning. In 2011, there were 128 cases of KLB. In 2013, in Riau province, PJAS was out of standard for 52 samples, with 2samples, 1 formalin sample, 1 rhodamin B sample, 21 physics and chemistry samples dan27 microbiology samples. It was really a bad situation. The objective of this research is to find out some related factors to the snacks choices at Sekolah DasarNegeri29 Pekanbaru Tangkerang Selatan Bukit Raya in 2017.This is a quantitative research with analysis survey by using cross sectional design. This research was done on May 2017 with respondents are class I, II, III, IV and V of SDN 29 Pekanbaru Tangkerang Selatan Bukit Raya. The data was collected by giving questionnaire and it was analyzed by using univariate and bivariate chi-square tests, and also it was processed by computer program. The result shows that there is relationship among knowledge (P value 0,002, nilai POR= 2,561), students’ attitude (P value 0,000, nilai POR = 3,291) and teachers’ role (P value 0,003, nilai POR= 3,007) to the food choice practice.Finally, the writer suggests to teachers of SDN 29Pekanbaru and health agency to do counseling program about healthy food. In other words, students’ negative attitude about food can be decreased. Then, teachers’ role in supervising healthy food like healthy canteen should be increased that it can be applied well in SDN 29 Pekanbaru in term of food choice practice.